EX-SITU CONSERVATION STRATEGY OF Cervus timorensis IN WEST JAVA, INDONESIA - Oktaviani, Eva; Ahmad Almulqu, Aah (Jurnal Biogenerasi, 2025)
This research was carried out to identify inhibiting and supporting factors with the aim of knowing internal and external factors and determining the ex-situ conservation strategy of Cervus timorensis in West Java, based on the calculation of the driving and inhibiting aspects in the management identified in the study using the SWOT analysis method. The results of the data were processed using SWOT analysis and calculating the value of internal factors (strengths, weaknesses) and external factors (opportunities - threats), the final score for internal factors was 1.18 and for external factors 0.44. These results determine the strategic direction of ex-situ conservation for Cervus timorensis in West Java which is located in quadrant I, which means a very favorable situation because it has opportunities and strengths with a high score so it must take advantage of the opportunities it has by maximizing existing strengths, and strategies that can implemented in this condition is to support an aggressive growth policy.